Volume 7A: Dynamics, Vibration, and Control 2020
DOI: 10.1115/imece2020-23723
|View full text |Cite
|
Sign up to set email alerts
|

Enhance PV Panel Detection Using Drone Equipped With RTK

Abstract: Solar energy is getting a lot of traction due to the reduced cost and friendlier to the environment compared to fossil fuel. It is essential to inspect the PV farms to ensure that the correct capacity produced through early PV fault detection. We proposed a full autonomous solution, where the drone mission is programmed to follow a specific Global Positioning System (GPS) waypoints. The collected videos will undergo various image processing techniques to detect and track the PV panels. In this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…As a result, precision (P) and mean average precision (mAP) increased by 6.3% and 9.4%, respectively, while the parameter count decreased by 62.65%. Compared to the SSD, Faster R-CNN [27], YOLO V3, and YOLO V4 models, precision (P) improved by 15.62%, 21.47%, 9.54%, and 13.75%, respectively, and mean average precision (mAP) improved by 13.%, 18.12%, 22.19%, and 11.8%, respectively. These comparative results demonstrate that the YOLOv5-BDL model achieves improved detection accuracy while maintaining superior performance in terms of memory and other software costs.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, precision (P) and mean average precision (mAP) increased by 6.3% and 9.4%, respectively, while the parameter count decreased by 62.65%. Compared to the SSD, Faster R-CNN [27], YOLO V3, and YOLO V4 models, precision (P) improved by 15.62%, 21.47%, 9.54%, and 13.75%, respectively, and mean average precision (mAP) improved by 13.%, 18.12%, 22.19%, and 11.8%, respectively. These comparative results demonstrate that the YOLOv5-BDL model achieves improved detection accuracy while maintaining superior performance in terms of memory and other software costs.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the validation set was held-out until the last test. Comparing the methods proposed in this paper with the five techniques discussed in the literature, which are the YOLOv3-based method from Tommaso et al [33], the Faster-RCNN-based method from Girshick et al [54], the SVM-based method from Mantel et al [32], the Mask-RCNN-based method from Almazroue et al [55], and the SSD-based method from Ren et al [56], the results showed that our performance on the Multi-Defect dataset was much better than the other models. The specific mAP performance is listed in Table 3.…”
Section: Comparison With Other Methods On the Multi-defect Datasetmentioning
confidence: 99%
“…Tommaso et al [33] 57.9 ± 0.07 Girshick et al [54] 69.3 ± 0.06 Mantel et al [32] 45.3 ± 0.07 Almazroue et al [55] 51.2 ± 0.06 Ren et al [56] 30.8 ± 0.06 Proposed GBH-YOLOv5 97.8 ± 0.02…”
Section: Methods Map (%)mentioning
confidence: 99%